Adverse effects of polychemotherapy for leprosy in 13 years of follow-up at a university hospital, - Violeta Duarte Tortelly; Egon Luiz Daxbacher; Arles Martins Brotas; Sueli Carneiro (Sociedade Brasileira de Dermatologia, 2021)
Abstract Leprosy is one of the neglected diseases in the world and Brazil is the second country with more cases. A retrospective study was conducted based on the medical records of 196 leprosy patients diagnosed during the course of 13 years at a university hospital. The aim was to describe the adverse effects of polychemotherapy, as well the most prevalent and most vulnerable populations. In the study, dapsone was the most implicated drug, especially in women, and the risk increased with age. The authors conclude that with this patient profile, greater vigilance should be taken regarding possible adverse effects, especially anemia.